The Discursive Construction of Terrorist Group Identity - Rothenberger, Liane; Müller, Kathrin; Elmezeny, Ahmed (Terrorism and political violence, 2018)
The media coverage of terrorist acts has been the subject of numerous scientific studies. However, the terrorist groups' own communication perspectives have not been thoroughly researched. The following article deals with terrorist groups and their use of websites for identity building. We examine the discursive construction of terrorist group identity through critical discourse analysis (CDA). The CDA of online texts from websites of terrorist groups is based on a five macro-strategy scheme. Our sample consists of six terrorist groups, with each group of two sharing different motivations: social-revolutionary, ethno-nationalist, or religious. All the groups analyzed are listed as terrorist organizations by the European Union. The CDA of 27 terrorist websites, purposively sampled, was conducted using two coders per site. Through this analysis, the researchers draw conclusions on strategies employed by terrorist organizations in building identity and how to counter their unregulated propaganda.